2018
DOI: 10.1212/wnl.0000000000006471
|View full text |Cite
|
Sign up to set email alerts
|

Use of newer disease-modifying therapies in pediatric multiple sclerosis in the US

Abstract: ObjectiveTo characterize the use and safety of newer disease-modifying therapies (DMTs) in children with multiple sclerosis (MS) and clinically isolated syndrome (CIS) treated under 18 years of age.MethodsThis is a cohort study including children with MS or CIS followed at 12 outpatient practices participating in the US Network of Pediatric MS Centers. DMT use, including duration, dose, and side effects, was analyzed. Newer DMTs were defined as agents receiving Food and Drug Administration approval or with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 35 publications
(49 reference statements)
6
54
1
4
Order By: Relevance
“…In addition to establishing effectiveness, a priority in studying DMTs in children includes evaluating safety. 40 In a prior study of this cohort, we reported similar short- term side effects of newer DMTs to those reported in adults, 30 although these may be underestimated due to reliance on database capture without homogeneous collection of safety data during visits. In this prior study, side effects were most common with dimethyl fumarate, including gastrointestinal side effects and rash; the most common side effects on natalizumab included headache and gastrointestinal symptoms; on rituximab, the most common side effects were rash and hypotension; there was 1 case of arrhythmia on fingolimod.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In addition to establishing effectiveness, a priority in studying DMTs in children includes evaluating safety. 40 In a prior study of this cohort, we reported similar short- term side effects of newer DMTs to those reported in adults, 30 although these may be underestimated due to reliance on database capture without homogeneous collection of safety data during visits. In this prior study, side effects were most common with dimethyl fumarate, including gastrointestinal side effects and rash; the most common side effects on natalizumab included headache and gastrointestinal symptoms; on rituximab, the most common side effects were rash and hypotension; there was 1 case of arrhythmia on fingolimod.…”
Section: Discussionmentioning
confidence: 59%
“…In this prior study, side effects were most common with dimethyl fumarate, including gastrointestinal side effects and rash; the most common side effects on natalizumab included headache and gastrointestinal symptoms; on rituximab, the most common side effects were rash and hypotension; there was 1 case of arrhythmia on fingolimod. 30 Longer follow-up with standardized collection of safety data is required to assess DMT safety in children, such as through open-label extension studies following pediatric clinical trials. 40 Additional safety data beyond those reported recently 30 are unfortunately not available for this cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While treatment patterns may vary, practice patterns in the United States have been evolving toward the earlier use of more potent therapies earlier in the disease course. 69…”
Section: Disease-modifying Therapiesmentioning
confidence: 99%
“…Für Natalizumab und Fingolimod liegen bereits umfangreiche Erfahrungen bei Kindern und Jugendlichen vor [6,7,11,14]. Hierbei spielen der John-Cunningham-Virus-Antikörper-Index (JCV, humanes Papillomavirus 2), die Anzahl der bisherigen Tysabri-Infusionen und eine evtl.…”
unclassified